General practitioner training in ENT in the Trent Region. - Veitch, D (1992)
A questionnaire was designed and posted to 220 general practitioners in the Trent Region. The questionnaire looked at the individual's undergraduate and postgraduate training. The results indicate that there is a great demand among final year vocational trainees and principals in general practice for an increase in the amount of formal postgraduate training in ENT. Nearly 85% of those questioned welcomed the opportunity of further training, primarily through attending courses, lectures or consultant clinics. Only 13% requested a formal attachment as an SHO on an ENT unit. Just over one in three of the respondents had received formal postgraduate training during their trainee years but even in this group 75% felt they would benefit from further training. Even at an undergraduate level, approximately half of the respondents commented that they had not received or undertaken examination of the ear, nose and throat in adults or children.